Design and implementation of a fuzzy logic based controller for refrigerating systems - Rashid, Muhammad Mahbubur; Islam, Ashraful (IEEE Explore, 2010)
This paper describes an intelligent the temperature control at a desired level in a refrigerator. The control works on the basis of modeling a thermostatic appliance and the use of fuzzy logic. A refrigeration system control device using fuzzy logic for controlling a plurality of refrigeration compressors such that the closest capacity is selected to match the load to each of a plurality of evaporators comprising, a control having an input adapted to be connected to a means to sense the temperature in the controlled space wherein a control signal is indicative of the maximum refrigeration load of the controlled space, a means for determining whether the primary control variable in said space is above or below a single predetermined desired target. Thermostatically simulated and fuzzy controlled model are presented successively. The latter is set-up on the basis of the Mamdani’s type of fuzzy rules. MATLAB, SIMULINK and Fuzzy Logic TOOLBOX (FLT) are the programming environments used for realization of the model. The principal aim in designing the control is to assure the fastest and best transition possible from an analogue to digital control of the refrigerating appliance, which represents the basis of a functional expansion demanded by the present market.